Targeting Rio: Enhancing the daily training environment in archery using technology - Chalkley, D.; Giblin, G.; Pepping, G.-J. (Journal of Fitness Research, 2016)
Skilled archers have demonstrated a greater ability to control their postural sway immediately before the arrow is released. This study examined the effect of training conditions on in-situ postural sway of elite archers. Three elite male archers shot 12 arrows at a regulation target while standing on a Tekscan Sports Balance Analyser. Data was collected in two conditions; standing on the ground; and standing on a raised platform. Postural sway was significantly higher in the anteroposterior direction when on the platform. The results highlight the need for athletes to replicate their competition environments in their daily training environments.